PTH-134 Setting Up An Endoscopy Unit in Northern Malawi. (17th August 2016) - Nyahoda, R; Uledi, S; Kibrete, W; Nyirenda, R; O'Toole, P; Gordon, MA; Stanley, AJ
Abstract : Introduction: There is a major need for endoscopic services in Malawi due to the very high incidence of both variceal bleeding related to schistosomiasis and gastro-oesophageal cancer. The availability of facilities and trained staff to perform variceal band ligation (VBL) and endoscopic stent insertion would benefit local patients. The aim of this project was to set-up an endoscopy unit at Mzuzu Central hospital (MCH), the regional hospital in Northern Malawi, which serves a population of approximately 2 million. Methods: After an initial assessment visit, four on-site training visits (two accompanied by endoscopy nurse trainers) were undertaken by a UK endoscopy trainer between 2012–2015. Endoscopy equipment was donated and shipped out from Glasgow. The local endoscopists and endoscopy nurses also attended formal endoscopy training courses at the recognised regional training centre in Blantyre. Malawi-adapted DOPS and unit GRS were undertaken and numbers of procedures audited. Results: During this period, six donated endoscopes and many accessories were delivered to MCH. Local clinicians and nurses had four weeks of on-site intensive training and attended five formal training courses. Skills in diagnostic endoscopy and VBL were taught and there was an introduction to stent insertion. A total of 20 DOPS were undertaken showing a gradual improvement in endoscopic skills. The unit GRS assessment improved with regard to patient consent, clinical monitoring, reporting and audit. A nine-month audit of consecutive endoscopic procedures at MCH revealed either varices or upper GI cancer in 28% cases. Over the total study period, the annual number of endoscopies undertaken at MCH increased from 108 to 376, with VBL cases increasing from 17 to 51. Conclusion: A functioning endoscopy unit has been set up at MCH with introductory skills provided to local endoscopists and nurses, by both on-site training and attendance at formal training courses. Advanced training of more endoscopists in therapeutic endoscopy and ongoing equipment support is required to ensure the unit becomes sustainable. Disclosure of Interest: None Declared